Knowledge, practice and perceived barriers towards chemotherapy induced nausea and vomiting in prophylaxis guideline adherence among nurses in oncology units at selected hospitals, in Addis Ababa, Ethiopia, a cross-sectional study - Deneke Gebre; Rajalakshmi Murugan; Ketema Bizuwork; Teshome Habte Wurjine (BMC, 2022)
Abstract Background Chemotherapy-induced emesis can be prevented by the use of recommended guidelines for antiemetic regimens but a research study indicates that in Ethiopia the use of standard antiemetic drug guidelines is very limited. Objectives To assess knowledge, practice, and perceived barriers towards chemotherapy-induced nausea and vomiting in prophylaxis guideline adherence among nurses in oncology units. Methods A cross-sectional study design was conducted among 81 oncology nurses selected in the two public hospitals of Addis Ababa, from March 1 to 30, 2020. The study participants were selected by using the population census method from the source population of nurses in oncology units. Data has collected by using semi-structured questionnaires with the self-administrated method. Data were analyzed by using Statistical Package for the Social Sciences software version 24. Descriptive statistics and logistic regression including bivariate and multivariate were conducted to examine the association between independent and outcome variables. The level of significance was determined at a p-value < 0.05 and a 95% confidence interval. Result Seventy-nine nurses participated with a 96% of response rate. All participants were aged greater than 24 with a mean age of 28.8 ± 6 years and nearly two-thirds of the respondents (60.8%) were females. Nurses were not trained in chemotherapy-induced nausea and vomiting management shows 54.4%. nurses' knowledge of chemotherapy-induced nausea and vomiting prophylaxis Guidelines was 78.5%. The means score of oncology nurses' practice toward guideline recommendation was 41.8%. Knowledge of nurses associated with the use of chemotherapy-induced nausea and vomiting prophylaxis guideline recommendations working in the outpatient department, inpatient ward, and chemotherapy administration unit has a significant association with chemotherapy-induced nausea and vomiting management knowledge. In the multiple logistic regression analysis, nurses who have trained for chemotherapy-induced nausea and vomiting management were 1.64-fold more aware than those who were not trained. Conclusion The study reveals that nurses working in the oncology unit of the study hospitals have a poor practice of Chemotherapy-Induced Nausea and Vomiting. Therefore, recommended providing Training for the Nurses working in the oncology unit and encourage them to apply standard guidelines.